1977
DOI: 10.1037/0021-9010.62.4.480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of expectation and disconfirmation on postexposure product evaluations: An alternative interpretation.

Abstract: Interpretations of the effect of expectation and disconfirmation on perceived product performance are reviewed. At issue is the relative effect of the initial expectation level and the degree of positive or negative disconfirmation on affective judgments following product exposure. Although the results of prior studies suggest a dominant expectation effect, it is argued that detection of the disconfirmation phenomenon may have been clouded by a conceptual and methodological overdetermination problem. To test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
886
0
64

Year Published

1990
1990
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,264 publications
(979 citation statements)
references
References 9 publications
29
886
0
64
Order By: Relevance
“…For example, in terms of differences, CS/D is also thought to have an affective component (Oliver 1993) and to be experiential; therefore, it is best judged after a purchase (Howard and Sheth 1969;Hunt 1977;Oliver 1993).' By comparison, in the literature value seems to be tied more closely to the specific concepts of costs and pricing, relative to quality.…”
Section: Evaluative Judgments: Satisfaction Value and Purchase Intementioning
confidence: 99%
See 3 more Smart Citations
“…For example, in terms of differences, CS/D is also thought to have an affective component (Oliver 1993) and to be experiential; therefore, it is best judged after a purchase (Howard and Sheth 1969;Hunt 1977;Oliver 1993).' By comparison, in the literature value seems to be tied more closely to the specific concepts of costs and pricing, relative to quality.…”
Section: Evaluative Judgments: Satisfaction Value and Purchase Intementioning
confidence: 99%
“…Churchill and Surprenant 1982;Oliver 1977Oliver , 1980. We do not test such causal linkages, have not collected data that speak to those linkages, or made any sort of conclusive statements regarding such linkages.…”
Section: Evaluative Judgments: Satisfaction Value and Purchase Intementioning
confidence: 99%
See 2 more Smart Citations
“…The study found that participants who felt a game failed to meet expectations rated the game negatively (on several affective measures), while those who felt it exceeded expectations gave positive ratings. Michalco et al framed their studies around the idea of expectation (Oliver, 1977) -a framework for contemplating the relationship between expectations and outcomes that was prevalent in marketing research in the 1970s and 80s. Expectation disconfirmation does not predict any empirical outcomes; rather, various adaptation theories (including contrast theory (Sherif, 1961), assimilation theory (Sherif, 1961), and cognitive dissonance theory (Festinger, 1957)) explain how disconfirmation is resolved into subjective preferences.…”
Section: Expectation Theorymentioning
confidence: 99%